SISTEM PEMANTAU DAN PENGATUR SUHU RUANG MENGGUNAKAN SENSOR LM35 BERBASIS ARDUINO UNO - , PRALISTYA RETNA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Has been made a monitoring and room temperature control system using a LM35 sensor that based on Arduino Uno which designed to make it easier to regulate and monitor the temperature of the room. This system consists of a LM35 temperature sensor, relay circuits, temperature sensor circuits and potentiometer with lcd, and the Arduino system. Monitoring the temperature of the room will be displayed through the LCD and the Short Message Service (SMS). The design of the room temperature setting using the pot as a setpoint. And room temperature using a lcd monitor, and Short Message Service (SMS). Software program that used is an Arduino Uno and Icomsat v1.1. Monitoring and regulatory system can be implemented using the Arduino Uno R3, Icomsat v1.1, and potentio. LM35 sensor is placed at one corner of the room is used to determine the temperature detected in the room. Data from the sensors will be displayed on the LCD and SMS. Blower and heater located in a room used to keep the temperature remains in the range specified by the setpoint potentiometer.